Analysis Science Process Skills Content in Chemistry Textbooks Grade XI at Solubility and Solubility Product Concept - Antrakusuma, Bayu; Masykuri, Mohammad; Ulfa, Maria (International Journal of Science and Applied Science: Conference Series, 2018)
The aim of this research was to determine the analysis of science process skills in textbooks of chemistry grade XI in SMA N 1 Teras, Boyolali. This research used the descriptive method. The instruments were developed based on 10 indicators of science process skills (observing, classifying, finding a conclusion, predicting, raising the question, hypothesizing, planning an experiment, manipulating materials, and equipment, Applying, and communicating). We analyzed 3 different chemistry textbooks that often used by teachers in teaching. The material analyzed in the book was solubility and solubility product concept in terms of concept explanation and student activity. The results of this research showed different science process skill criteria in 3 different chemistry textbooks. Book A appeared 50% of all aspects of science process skills, in Book B appeared 80% of all aspects of science process skills, and in Book C there was 40% of all aspects of the science process skills. The most common indicator in all books was observing (33.3%), followed by prediction (19.05%), classifying (11.90%), Applying (11.90% ), planning experiments (9.52%), manipulating materials and equipment (7.14%), finding conclusion (4.76%), communicating (2.38%). Asking the question and hypothesizing did not appear in textbooks.